Tom Patterson y los orígenes de la civilización peruana temprana - Burger, Richard (2024)
Thomas C. Patterson is a significant figure in the history of Peruvian archaeology. This article reviews some of his contributions with an emphasis on his work on early Andean civilization. Beginning in the 1960s he focused along with Edward Lanning on the settlement patterns and economic systems of the central coast, especially those of the Preceramic (or Archaic). This work shed light on the interdependence of shoreline dwellers and inland farmers. It also produced information on the Lima culture, a subject that served as the basis for his doctoral dissertation at the University of California, Berkeley under the supervision of John Howland Rowe. Patterson’s subsequent excavations at the shoreline site of Ancón, his survey of the Lurin Valley and his visits to previously known early sites helped to clarify the pottery sequence of the central coast and the Initial Period and to demonstrate that the pre-Chavin pyramid complexes such as Huaca La Florida predated the fluorescence of Chavin de Huantar. His thinking has continued to evolve and his later work uses Marxist theory to better understand the emergence of early Andean societies on the coast and the rise and fall of the Incas. Utilizing the historically specific concept of social formations rather than more common neo-evolutionary stages, he has demonstrated that the builders of the monumental U-shaped pyramid complexes were not chiefdoms nor states as had been claimed. These writings demonstrate the value of utilizing perspective of historical materialism to interpret Peru’s archaeological record.